Government subsidies and income smoothing - Pappas, Kostas; Walker, Martin; Xu, Alice Liang; (Colin) Zeng, Cheng (Contemporary Accounting Research, 2024)
Abstract This study examines the relationship between government subsidies and income smoothing using a sample of US‐listed firms. We find that subsidized firms smooth their earnings more aggressively than their unsubsidized peers. This finding is consistent with the reasoning that subsidized firms bear higher political costs and have more incentives to smooth earnings to avoid public attention. In addition, smoothing by subsidized firms is more pronounced when the subsidies are granted through non‐tax‐related channels than through tax‐based channels, and the positive association between government subsidies and income smoothing is stronger for firms under higher public scrutiny and with less transparent information environments. Further analysis shows that smoothing by subsidized firms serves mainly to obfuscate earnings and that subsidized firms that smooth earnings tend to continue receiving subsidies in the future. Overall, our results help explain the role of government subsidies in shaping firms' accounting and disclosure choices.